DOES THE FREQUENCY OF ACUTE CHOLECYSTITIS DECREASE DURING THE RAMADAN MONTH? - Murat SEYIT; Atakan YILMAZ; Sevda YILMAZ; Mert OZEN (International Journal of Health Services Research and Policy, 2021)
The pathophysiological mechanism of acute cholecystitis (AC), which is essentially the inflammation of the gallbladder, is blockage of the cystic duct, and its most common cause is gallstones. On the other hand, fasting held in Ramadan is worship practiced by Muslims within the period from dawn to sunset by avoiding any eating and drinking act. Within this framework, our study ultimately intends to reveal the variation of AC in two different time periods. We retrospectively compared the demographic characteristics, admittance times, biochemical parameters of the subjects diagnosed with AC and hospitalized in the general surgery between 2012 and 2018. We also evaluated diagnosis classification, length of hospitalization, presence of intensive care stay, presence of operation during hospitalization, and the underlying comorbid diseases of the subjects. 225 patients were hospitalized in the general surgery service after being diagnosed with AC in the ED over the course of six years, yet the total number of subjects recruited for the study is 46. Whereas 10 patients (21.7%) were admitted and hospitalized during the Ramadan month, 36 (78.3%) patients in the other group were hospitalized one month before and after Ramadan. 16 (34.8%) of the hospitalized patients underwent emergency surgery, while 30 (65.2%) patients were operated on electively. The comparison of the two cohorts in our study revealed no significant difference in relation to the demographic characteristics, laboratory findings, imaging methods, underlying comorbid diseases, and the length of hospital stay. Nevertheless, clinical investigations seem to have revealed a difference between groups.